Pengaruh Current Ratio Dan Perputaran Piutang Terhadap Return On Asset Pada PT. Dharma Satya Nusantara, Tbk - Jelunut, Virgula; Aditya Dzulfadeln, Prawira; Purnama Alam, Andi Rifqah (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine the effect of current ratio and receivables turnover on return on assets at PT. Dharma Satya Nusantara, Tbk. The types of data used are qualitative and quantitative data. The data sources used are secondary data. The analysis method used is multiple linear regression analysis, coefficient of determination, correlation coefficient, f-test and t-test. The results of the study show the regression equation Y = -1.85 + 0.05X1 + 0.07X2, coefficient of determination of 19.23%, correlation coefficient of 0.4385. It is concluded that simultaneously the current ratio and receivables turnover have no significant effect on return on assets and partially the current ratio has a positive and insignificant effect on return on assets, while receivables turnover has a positive and insignificant effect on return on assets at PT. Dharma Satya Nusantara, Tbk. So the proposed hypothesis is rejected.